The Mertiyo Rathors of Merto, Rajastha select translations bearing on the history of a Rajput family, 1462-1660, volumes 1-2 - Saran, Richard Davis; Ziegler, Norman Paul (Michigan papers on South and Southeast Asian studies, 2001)
This book is a treasure for scholars of Rajput history. Richard D. Saran and Norman P. Ziegler, whose contributions to Rajput studies are well known to specialists in the field, have given us a work of deep and exacting scholarship. It is the culmination of decades devoted to the study of Middle Marwari chronicles from Rajasthan. The sources translated here provide access to the fortunes of a branch of the Jodhpur royal family, and in doing so they illuminate the larger world of Rajputs in the middle period.